2021
DOI: 10.3389/fpubh.2020.603217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contamination of Freshwater Habitat With Common Heavy Metals and Anions on the Prevalence of Human Adenoviruses and Enteroviruses

Abstract: The occurrence and survival of enteric viruses in open surface waters can be impacted by a host of factors including fecal emission levels, seasonal variations, virus stability and the physicochemical parameters. In this research, we aimed to document the association between contaminations of water samples with human enteric viruses (adenoviruses and enteroviruses) from a freshwater lake with variations in chemical contaminants. We collected 216 water samples from October 2010 to April 2012, from a 4 km stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…( Haramoto et al., 2018 ) found that the most abundant class of enteric viruses was different on different types of matrices, indicating that systemic pollution influences community structure and composition. This supports the observation of ( Wasonga et al., 2021 ) and suggests that the matrix with high faecal pollution levels and minerology influences the viral community composition. Even less research has been done on other viral families, like hepatoviruses, as indicators of faecal pollution than on other environmental viruses and bacteria.…”
Section: Regional Studies Of Environmental Virology and Public Healthsupporting
confidence: 90%
See 1 more Smart Citation
“…( Haramoto et al., 2018 ) found that the most abundant class of enteric viruses was different on different types of matrices, indicating that systemic pollution influences community structure and composition. This supports the observation of ( Wasonga et al., 2021 ) and suggests that the matrix with high faecal pollution levels and minerology influences the viral community composition. Even less research has been done on other viral families, like hepatoviruses, as indicators of faecal pollution than on other environmental viruses and bacteria.…”
Section: Regional Studies Of Environmental Virology and Public Healthsupporting
confidence: 90%
“…Studies from other regions of the country support the notion that changing the composition of some viral gene groups is a typical response to pollution, and a similar change in relative abundance has been observed in hydro-chemically contaminated areas of a freshwater matrix (Wasonga et al, 2021). However, because these observations are based on a small number of studies, it is challenging to predict with certainty the changes that will probably be seen in other environmental matrices and settings.…”
Section: Regional Studies Of Environmental Virology and Public Healthmentioning
confidence: 98%